THE ROLE OF FIRM CHARACTERISTICS AND AUDIT COMMITTEE SIZE IN TIMELINESS OF FINANCIAL REPORTIN - Merryani, Merryani; Astarani, Juanda (Jurusan Akuntansi, Fakultas Ekonomi dan Bisnis, Universitas Tanjungpura, 2018)
This study examines the relationship of firm characteristics and audit committeesize with Timeliness of Financial Reporting (TIML) among retailer trade companies listed in Indonesian Stock Exchange. This study focuses on three variables of firm characteristics (i.e., firm size, profitability, and leverage) and one variable of corporate governance (i.e., audit committee size). A quantitative method of analysis, secondary data from annual reports for the period of 2012 to 2016, and purposive sampling, was adopted. The results revealed that both profitability and leverage are negatively associated with TIML, yet no significant association was found regarding the firm size and audit committee size with TIML. On the other hand, the results also revealed that firm size, profitability, leverage, and audit committee size could enhance TIML since those variables are found to be simultaneously associated with TIML.Keywords: Timeliness, Financial Reporting, Reporting Lag